The Moderating Effect of Competitive Advantage on the Relationship of Intellectual Capital and Financial Performance - Setyaningrum, Ayu; Pratama, Bima Cinintya; Wahyuni, Sri; Winarni, Dwi (E-Jurnal Akuntansi, 2025)
This study examines the effect of Intellectual Capital components: Human Capital, Structural Capital, and Physical Capital on Financial Performance, while assessing the moderating role of Competitive Advantage. The population consists of banking companies listed on the Indonesia Stock Exchange and Commercial Bank of Malaysia from 2020-2023. A total of 264 observations were selected using purposive sampling based on predefined criteria. Panel data regression analysis using Stata software shows that Human Capital and Physical Capital have a positive and significant effect on ROA, while Structural Capital and Competitive Advantage do not. Moreover, Competitive Advantage significantly moderates the relationship between Physical Capital and ROA. Keywords: Intellectual capital components; Competitive advantage; Financial performance.